Influence of addition of zirconia on PMMA: A systematic review - Leão, Rafaella de Souza; Moraes, Sandra Lúcia Dantas de; Gomes, Jéssica Marcela de Luna [UNESP]; Lemos, Cleidiel Aparecido Araújo; Casado, Bruno Gustavo da Silva; Vasconcelos, Belmiro Cavalcanti do Egito; Pellizzer, Eduardo Piza [UNESP] (Elsevier, 2020)
The objective of this systematic review is to evaluate the effect of the incorporation of zirconia (ZrO2) particles on the mechanical properties of PMMA (polymethyl methacrylate), and to establish which characteristics of this material yield the best results aiming their biomedical applicability. This study was carried out in accordance with the Items of Preferred Reports for Systematic Reviews and Meta-Analyzes (PRISMA) and is registered in PROSPERO under registration number: CRD42018095801. The searches were carried out in the PubMed, MEDLINE, Scopus and Cochrane Library databases for articles published up until April 2018. After the different stages of the article selection process, eight articles were selected for qualitative and quantitative analysis. All were in vitro studies, totaling 536 evaluated samples. The concentrations of zirconia ranged from 0.5% to 20% and the particle sizes were between 15 nm and 10 μm. The incorporation of zirconia particles did not increase the flexural strength of PMMA in only one study. While the concentration of zirconia influences PMMA, the type of acrylic resin, size, and silanization of zirconia particles did not influence the results. Thus, the addition of zirconia particles showed a positive effect on PMMA enhancing their use in the medical and dental field, especially when certain anatomical areas requires higher strength of the materials, providing longevity for the rehabilitation.
Keywords: Polymethyl methacrylate; Systematic review; Zirconium oxide